Impact of correcting the 2D PISA method on the quantification of functional tricuspid regurgitation severity . (23rd June 2022) - Tomaselli, Michele; Badano, Luigi P; Menè, Roberto; Gavazzoni, Mara; Heilbron, Francesca; Radu, Noela; Caravita, Sergio; Baratto, Claudia; Oliverio, Giorgio; Florescu, Diana R.; Parati, Gianfranco; Muraru, Denisa
Abstract: Aims: In functional tricuspid regurgitation (FTR) patients, tricuspid leaflet tethering and relatively low jet velocity could result in proximal flow geometry distortions that lead to underestimation of TR. Application of correction factors on two-dimensional (2D) proximal isovelocity surface area (PISA) equation may increase its reliability. This study sought to evaluate the impact of the corrected 2D PISA method in quantifying FTR severity. Methods and results: In 102 patients with FTR, we compared both conventional and corrected 2D PISA measurements of effective regurgitant orifice area [EROA vs. corrected (EROAc )] and regurgitant volume (RegVol vs. RegVolc ) with those obtained by volumetric method (VM) using three-dimensional echocardiography (3DE), as reference. Both EROAc and RegVolc were larger than EROA (0.29 ± 0.26 vs. 0.22 ± 0.21 cm 2 ; P < 0.001) and RegVol (24.5 ± 20 vs. 18.5 ± 14.25 mL; P < 0.001), respectively. Compared with VM, both EROAc and RegVolc resulted more accurate than EROA [bias = −0.04 cm 2, limits of agreement (LOA) ± 0.02 cm 2 vs. bias = −0.15 cm 2, LOA ± 0.31 cm 2 ] and RegVol (bias = −3.29 mL, LOA ± 2.19 mL vs. bias = −10.9 mL, LOA ± 13.5 mL). Using EROAc and RegVolc, 37% of patients were reclassified in higher grades of FTR severity. Corrected 2D PISA method led to a higher concordance of TR severity grade with the VM method ( ĸ = 0.84 vs. ĸ = 0.33 for uncorrected PISA, P < 0.001). Conclusion: Compared with VM by 3DE, the conventional PISA underestimated FTR severity in about 50% of patients. Correction for TV leaflets tethering angle and lower velocity of FTR jet improved 2D PISA accuracy and reclassified more than one-third of the patients. Graphical Abstract: Graphical Abstract Compared to the volumetric method by 3DE, the conventional PISA underestimated functional tricuspid regurgitation severity in about 50% of patients. Correction for tricuspid valve leaflets tethering angle and lower velocity of functional tricuspid regurgitation jet improved 2D PISA accuracy and reclassified more than one third of the patients.